The Research on the effectiveness of visual in the manual guide of digital camera - Wong, Vincent Thian Fook (Universiti Malaysia Sarawak (UNIMAS), 2007)
The researcher believes that the power of visual image is much more powerful and effective as a communication. Thus, "VISTURE" is created to help user learn and understand the Manual Guide of Digital Camera clearly and effectively. The final output is style of display and combining media to help consumer understand the guide conveniently.